2019
DOI: 10.3855/jidc.10583
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of antibodies and lymphocytes in pulmonary tuberculosis patients with negative and positive cultures

Abstract: Introduction: The sputum smear or the culture are the definitive diagnosis of pulmonary tuberculosis. Only a fraction of clinical patients are culture-confirmed. Methodology: A total of 24 clinical cases (40 ± 14 years old) with positive smear and negative co-morbidity were studied. Cases were selected from 600 patients who attended the pneumology service over two years. A sputum sample was cultured in Löwenstein-Jensen medium with consequent amplification of the rrnA V2 promoter, the differentiation reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
3
0
0
Order By: Relevance
“…The results of this study showed that LY, ALB, and PA were significantly lower in the case group as compared to the control group ( P < .05); while NE, MO, CRP, FIB, ESR, NLR, PII, and SIRI were significantly higher in the case group ( P < .05). This was consistent with the findings of Cázares-Sosa FR et al [ 22 ] and An HR et al [ 23 ] Reduction in LY count occurs since T lymphocytes limit MTB growth by cracking the MTB-infected cells. [ 24 ] Increased NE is associated with decreased LY.…”
Section: Discussionsupporting
confidence: 92%
“…The results of this study showed that LY, ALB, and PA were significantly lower in the case group as compared to the control group ( P < .05); while NE, MO, CRP, FIB, ESR, NLR, PII, and SIRI were significantly higher in the case group ( P < .05). This was consistent with the findings of Cázares-Sosa FR et al [ 22 ] and An HR et al [ 23 ] Reduction in LY count occurs since T lymphocytes limit MTB growth by cracking the MTB-infected cells. [ 24 ] Increased NE is associated with decreased LY.…”
Section: Discussionsupporting
confidence: 92%
“…The total lymphocyte count of tuberculosis patients in the low PNI group was reduced, which was consistent with the results of Cazares-Sosa et al. ( Cázares-Sosa et al., 2019 ). Patients with tuberculosis have disordered immune status.…”
Section: Discussionsupporting
confidence: 92%
“…Similar to tumor patients, tuberculosis patients with low PNI have low immune function, characterized by high NLR, MLR, and PLR, and PNI was negatively correlated with immune ratio (NLR, MLR, and PLR). The total lymphocyte count of tuberculosis patients in the low PNI group was reduced, which was consistent with the results of Cazares-Sosa et al (Caźares-Sosa et al, 2019). Patients with tuberculosis have disordered immune status.…”
Section: Association Between Pni and Ns In Tb Patientssupporting
confidence: 91%